FACTORS AFFECTING THE ADOPTION OF E-COMMERCE: A STUDY OF RUBBER MSMES IN PUNE - et. al., Pitanjal Dutta (International Journal of Modern Agriculture, 2021)
Being one of the major sunrise sectors, the Indian Rubber Industry has emerged as a significant player in the Indian economic growth story. Its role as a key growth player can be highlighted by the domination of the small-scale sector in manufacturing the rubber products. The small sector enterprises account for 90% of the 6000 plus rubber product manufacturing units and over 50% production of rubber goods in the non-tyre category. Similarly, around 40% of the rubber products export comes from the small-scale sector. Previous studies have demonstrated that the collaboration between E-commerce and rubber small sector enterprises can help in supporting the upturn experienced in recent years. However, many micro, small, and medium-scale enterprises (MSMEs) dealing with the production and processing of rubber merchandise are nonetheless reluctant to choose E-Commerce to enhance their national and international commodity chain. Hence, this paper centres around understanding the reasons behind the hesitance of such MSMEs. For the examination, the information was gathered through organized meetings of proprietors of elastic items assembling and handling firms of rubber industry in Pune. During February-March 2018, a deliberately chosen test of 50 MSMEs (10 adopters of internet business and 40 non-adopters) was taken up for the examination. After treating the data with statistical tools, the paper found that the scale of operations and technical know-how of the owner/manager has a positive impact whereas market competitiveness individually does not impact the adoption of E-Commerce. Also, favourable government policies have been found to boost E-Commerce adoption by firms. In this regard, the paper helps in identifying the important factors which influence the rubber industry's marketing strategy and the primary reasons behind adopting or not adopting E-Commerce.